Enteric methane emission from Sheep fed with rhodes grass hay (Chloris gayana) alone or supplemented with dried distillers’ grains with solubles - Gere, José Ignacio; Feksa Frasson, Mónica; Wawrzkiewicz, Marisa; Fernández Pepi, María Gabriela; Ramos, María Laura; Bualo, Ricardo Alberto; Ceron Cucchi, Maria Esperanza; Jaurena, Gustavo (MDPI, 2022)
Livestock systems based on subtropical and tropical pastures are characterized by the low productivity of livestock due to the poor nutritional value of the forage (low nitrogen concentration and digestibility, and high fiber and lignin concentrations). These conditions lead to low productivity and, consequently, high absolute emissions of methane (CH4) per unit of product. Dry distilled grains with solubles (DDGS) are the main by-product resulting from ethanol production, and they are characterized by their high-energy fibrous and protein content, thus becoming an option for the supplementation of low-quality forage. This research investigated the effects of dietary DDGS inclusion on dry matter digestibility (DMD) and enteric CH4 emission. Eight adult sheep of 64 ± 8 kg live weight were used. The duration of the study was 54 days, divided into two periods (changeover design), which comprised a 17-day pre-experimental period and 10 days for experimental data collection. Animals were allocated to one of two treatments used: hay (H) as a control treatment, where animals were fed with Rhodes grass hay alone; and H + DDGS, where animals were fed with H supplemented with DDGS. CH4 emissions were estimated using the sulfur hexafluoride (SF6) tracer technique. Diets containing DDGS increased DMI by 22% (p < 0.05) and reduced daily CH4 emissions by 24% (g/d), the CH4 yield by 35% (g/kg DMI), and the average value of CH4 energy per gross energy intake (Ym) by 44%, compared to the control treatment (p < 0.05). The experiment demonstrated that supplementation with DDGS in low-quality roughage reduced daily CH4 emissions, yields, and Ym. View Full-Text